Film seeds coating with hexane extracts from Illicium verum Hook.f. and Syzygium aromaticum (L.) Merrill & Perry for controlling Callosobruchus maculatus (F.) and Callosobruchus chinensis L - J. Pumnuan; K. Sarapothong; Potjana Sikhao; Chutichot Pattamadilok; A. Insung (Pest Management Science, 2021)
BACKGROUND: The application of film seed coating with some plant extracts against stored insect pests was an alternative approach for insect protection instead of using chemical insecticides. The overuse of insecticides has contributed to both human health and environmental problems. The hexane extracts of Illicium verum (HS) and Syzygium aromaticum (HC) were evaluated against bruchid beetles (Callosobruchus maculatus and Callosobruchus chinensis). The insecticidal activities and enhancing seed germination after being coated by various concentrations of extracts, purified fraction (PF) of extracts, standard chemicals of PF, fipronil insecticide (FI), and coating agent groups were evaluated after stored. RESULTS: values of 1.60-1.90 and 3.44-3.62 h, respectively. They could also kill those insects with a higher number than that of standards. The HS and HC could inhibit the progeny population of those insects over 95.6% with no significant difference compared to the FI group. The eugenol standard was the most effective and completely inhibited the emergence compared with trans-anethol standard and PFs. The seed that was coated with 1% of HS and stored at 4 °C for 6 months showed no effect on seed germination with no significant difference between FI and control groups. CONCLUSION: The application of 1% of HS incorporated in the film seed coating against bruchid beetles and did not affect seed germination quality after 6 months. © 2021 Society of Chemical Industry.
Keywords: Insect Pest Control Strategies; Phytochemical compounds biological activities; Plant Growth Enhancement Techniques